2022
DOI: 10.3389/fpsyt.2022.902245
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health of Children With Attention Deficit and Hyperactivity Disorder and Their Parents During the COVID-19 Lockdown: A National Cross-Sectional Study

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has caused a real disruption of children's lives. Children with neurodevelopmental disorders and their parents seem to be particularly vulnerable to adverse mental health effects due to lockdown policies. This study explores the psychological state of children with Attention Deficit Hyperactivity Disorder (ADHD) and their parents during the first lockdown in France. A national prospective cross-sectional parent-reported study was conducted using an online survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
15

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 18 publications
2
21
0
15
Order By: Relevance
“…A Canadian online survey to caregivers of children with ADHD aged 5-18 years (n = 587 surveys) revealed that during the COVID pandemic, parents reported that their children with ADHD experienced greater ADHD symptoms, depression and anxiety [13]. This finding of worsening ADHD symptoms in children diagnosed with ADHD during the COVID pandemic is consistent with other international studies from China [23] and France [24]. A systematic review of 12 studies (before February 25, 2021) from 9 countries involving 3,028 participants aged 4-27 years diagnosed with ADHD reported increased ADHD symptoms and psychological difficulties during the COVID pandemic [15].…”
Section: Introductionsupporting
confidence: 79%
“…A Canadian online survey to caregivers of children with ADHD aged 5-18 years (n = 587 surveys) revealed that during the COVID pandemic, parents reported that their children with ADHD experienced greater ADHD symptoms, depression and anxiety [13]. This finding of worsening ADHD symptoms in children diagnosed with ADHD during the COVID pandemic is consistent with other international studies from China [23] and France [24]. A systematic review of 12 studies (before February 25, 2021) from 9 countries involving 3,028 participants aged 4-27 years diagnosed with ADHD reported increased ADHD symptoms and psychological difficulties during the COVID pandemic [15].…”
Section: Introductionsupporting
confidence: 79%
“…The median quality score was 8 (range 3 (Buzzi et al, 2020) to 9 (Bram et al, 2020; Zheng et al, 2020)). Ten studies assessed the mental health outcomes in children and adolescents during COVID-19 (Bobo et al, 2020; Buzzi et al, 2020; Chen et al, 2020; Colizzi et al, 2020; Pınar Senkalfa et al, 2020; Saddik et al, 2020; Saurabh and Ranjan, 2020; Xie et al, 2020; Zheng et al, 2020; Zhou et al, 2020), mostly focused on depression and anxiety rates (Chen et al, 2020; Pınar Senkalfa et al, 2020; Saddik et al, 2020; Xie et al, 2020; Zheng et al, 2020; Zhou et al, 2020). Four studies assessed the impact on vaccination rates (Bramer, 2020; Chandir et al, 2020; McDonald et al, 2020; Santoli et al, 2020) and another four assessed impacts on health care use, including paediatric emergency healthcare department visits (Angoulvant et al, 2020; Bram et al, 2020; Bressan et al, 2020; Li et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Vulnerable groups. Specific groups of children were examined in three studies (Bobo et al, 2020;Colizzi et al, 2020;Pınar Senkalfa et al, 2020). The first assessed children with cystic fibrosis (CF), and found that they experienced lower levels of anxiety than children without CF (Pınar Senkalfa et al, 2020).…”
Section: Impact On Mental Healthmentioning
confidence: 99%
“…As it was shown in the extract, the term neurodivergent was used interchangeably with mental illness without any explanation. Overall, cnn.com less covered ADHD-related neurodiversity compared to bbc.com as its total neurodiversity score ( 5) is far less than bbc.com's (14). On the other hand, although bbc.com incorporated more neurodiversity frames, it rarely featured the neurodiversity terms such as neurodiverse or neurodivergent.…”
Section: Resultsmentioning
confidence: 95%
“…Increased adverse outcomes of the infection, higher rates of hospitalization, and mortality from COVID-19 have been associated with ADHD [10]. ADHD as a potential risk factor for COVID-19 infection [11] has been analyzed particularly in terms of the cross-infuence of ADHD and COVID-19, negative efects, and exacerbated symptoms [12][13][14][15]. Another study revealed the efects of digital media use on children and adolescents with ADHD on the core symptoms, worse attention, oppositional defant, behavior and emotional problems, and more self-reported anxiety and depression [16].…”
Section: Introductionmentioning
confidence: 99%